Assessment of knowledge, attitude and practice of smallholder farmers on market-oriented sheep fattening in North Shewa, Ethiopia - Wamatu, Jane; Ekule, Muluken; Mebratie, Anagaw (International Center for Agricultural Research in the Dry Areas, 2022)
A baseline survey of knowledge, attitude, and practice towards market-oriented sheep fattening in North Shewa Zone, Amhara Regional State, Ethiopia. A preliminary report